Marine Chitin 2019 - Sashiwa, Hitoshi (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
In 2019, we sent out a call for submissions to a Special Issue of Marine Drugs entitled "Marine Chitin 2019", and we are pleased that this issue has now been published. Over 16 high-impact papers were included in this issue, which we now plan to publish as a book. In addition, we now seek to publish a further Special Issue of Marine Drugs, "Marine Chitin 2020-2021". As before, we plan to produce an authoritative and exciting issue that will encompass breakthroughs in scientific and industrial chitin and chitosan research. Significant advances in chitin and chitosan research have been made since the 1970s, and current overviews in recent publications involving chitin and chitosan research advances are in need of an update.